Perfil clínico e epidemiológico da hanseníase em menores de 15 anos no estado do Maranhão, 2011 a 2021 - Valéria de Jesus Menezes de Menezes; Thajison Robert Menezes de Holanda;; Celijane Melo Rodrigues; Layanne Silva Oliveira; Ana Maria Almeida Silva Carvalho; Monica Elinor Alves Gama; Rebeca Costa Castelo Branco (Residência Pediátrica)
OBJECTIVE: To understand the epidemiological behavior and clinical profile of leprosy cases in children under 15 years of age, in the state of Maranhão in Brazil, between 2011 and 2021. METHODOLOGY: Epidemiological, descriptive study with a quantitative approach, based on retrospective data recorded in the Notifiable Diseases Information System / Ministry of Health of Brazil. RESULTS: It was found that in the period between 2011 and 2021, 3,918 cases of leprosy were registered in the age group of 1 to 14 years in the state of Maranhão in Brazil, of which 53.9% were male; 45.4% attended the 5th to 8th grade of elementary school; 69.6% were brown. The dimorphic clinical form was present in 45.7% of cases and 69.6% did not have a reactional episode. Multibacillary cases represented 59.9%; 71.7% had no disabilities while 12% had a Grade I disability. After discharge due to cure, 46.5% had no disability; blank variable represented 35.9% of cases. The polychemotherapy regimen MDT/MB/12 doses was used in 59.7% of participants. CONCLUSION: There is a need to implement educational actions about the disease, so that the population knows about transmission, prevention and treatment, where it is up to the State to mobilize resources that can be invested in public policies aimed at health education, and thus promote the access to adequate diagnosis and treatment.